Adam Lityński, O prawie i sądach początków Polski Ludowej, 1999 - Tadeusz Maciejewski (Czasopismo Prawno-Historyczne, 1999)
Recenzja: A. Lityński, O prawie i sądach początków Polski Ludowej, Białystok 1999, ss. 278.